Analysis of the Importance of Criteria in Carrier Selection - Jakubiak, Michał (Analiza ważności kryteriów wyboru przewoźnika, 2009)
The author made an attempt to verify, quoted in the expert literature, the recom-mendations devoted to the selection of a unit which provides transport services. The basis for the present study is a survey which main task is to identify the key criteria of carrier selection. The above mentioned survey was inspired by papers of Coyl, Bardy, and Langley. Following the results of the survey we can come to several conclusions. There can be observed a connection between the choice of criteria and the expectation of the environment in which the selection is carried, as well as the change of preferences of carrier selection in the last few years. Key words: logistics, carrier selection, supply chain management
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 65, s. s. 105-115
Keywords: logistics; carrier selection, supply chain management